Transfinite interpolations and Eulerian/Lagrangian dynamics - Garon, André; Delfour, Michel C. 1943- (Society for Industrial and Applied Mathematics, SIAM, 2022)
From finite to transfinite interpolations -- IDW and transfinite Barycentric interpolations -- Transfinite mean value interpolation -- Kriging and radial basis functions -- Dynamical transfinite interpolation -- Explicit moving mesh computations -- Moving mesh in monolithic fluid structure interaction -- Shape derivatives, velocity method, and interpolation -- Shape derivative via one-sided derivatives of minima and minimax
Includes bibliographical references and index
Keywords: Transfinite numbers; Interpolation; Dynamics; Lagrange equations